An Investigation into the use of Health Services in Wales by those who Self–report Disability using Linked Data: IJPDS (2017) Issue 1, Vol 1:140, Proceedings of the IPDLN Conference (August 2016) - Ahern, Aideen; Jones, Melanie (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Disability is strongly related to employment disadvantage (Berthoud, 2008). There is a scarcity of disability research within labour economics, therefore this project will add to the evidence gap by examining existing survey data linked to medical data. As part of a wider empirical investigation into the influence of disability on economic outcomes using survey data, we examine the additional value of linked data. This analysis of linked data is aimed to form an initial exploratory project to identify the potential benefits and limitations of data linking in this context. The work aligns closely with the WG Programme to Maximise the Use of Existing Data which seeks to explore how the Welsh Government can potentially use linked data to improve the evidence base for policymaking. The findings will feed into the evidence base relating to the Programme for Government. This project hopes to increase the understanding of the relationships between disability and employment, to further inform policy makers and to create awareness among researchers of the benefits of using linked data. Approach The project will involve examining the different patient pathways for those who self-report disability in the National Survey for Wales (NSW) 2012-15. The proposal therefore involves linking data (using SAIL)at the individual level from administrative data including records from the Welsh Demographic Service, GP event data, Patient Episode Database for Wales and A&E data to individual level responses in the NSW. The aim of this project is to examine differences in objective health indicators, such as number of GP activity between those who currently self-report disability (limiting long-standing illness), and those who do not. In addition, we will explore the effects that disability status has on employment status within Wales. While social and economic disadvantage associated with disability is frequently identified using self-reported information on disability in survey data, far less is known within social science about the medical history/conditions of these individuals. It will also be possible to control for/examine the interaction with a range of other demographic characteristics (age, gender etc) which are available in the NSW. Results Individuals in Wales who self-report disability use primary and secondary health services more so than non-disabled individuals. Conclusion This work has the potential to contribute significantly to the Employment, Education and Wellbeing Work package (RP2) of the ADRC-W.